Index numbers in theory and practice - Allen, R. G. D. (London : Macmillan, 1975)
This work deals with some further problems in the construction of index numbers, problems which are both troublesome and largely unresolved. These include the use of sampling techniques in index-number design and the theoretical and practical treatment of quality changes. It is also devoted to a number of detailed and specific applications of index-number techniques to problems ranging from national-income accounting, through the measurement of inequality of incomes and international comparisons of real incomes, to the use of index numbers of stock-market prices. Aimed primarily at students of economics, whatever their age and range of interests, this work will also be of use to those who handle index numbers professionally.
Includes index.
Includes bibliographical references: p. 270-274.
rpm 10/07/2017
Loans
Keywords: Index numbers (Economics)